2021
DOI: 10.51847/1ufxsztr6m
|View full text |Cite
|
Sign up to set email alerts
|

Side effects following COVID-19 vaccination: A cross-sectional survey with age-related outcomes in Saudi Arabia

Abstract: This is an open access journal, and articles are distributed under the terms of the Creative Commons Attribution-Non Commercial-ShareAlike 4.0 License, which allows others to remix, tweak, and build upon the work non-commercially, as long as appropriate credit is given and the new creations are licensed under the identical terms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 17 publications
1
14
0
Order By: Relevance
“…Sampling biases based on age could have occurred as older individuals are less likely to have Internet access or computer skills. However, comparable studies link this finding to the more robust immune response and more pronounced cytokine production in younger individuals compared to older individuals [ 6 , 7 ]. El-Shitany et al observed that those under 60 experienced more flu-like symptoms [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sampling biases based on age could have occurred as older individuals are less likely to have Internet access or computer skills. However, comparable studies link this finding to the more robust immune response and more pronounced cytokine production in younger individuals compared to older individuals [ 6 , 7 ]. El-Shitany et al observed that those under 60 experienced more flu-like symptoms [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Even with the advent of vaccinations for COVID-19, public health measures to avoid the transmission of the virus are still an important mainstay for preventing disease spread, as well as the emergence of new variants [11,12]. Knowledge about the disease is essential to modifying attitudes and practices, which is an important step in curtailing the spread of infection [13,14]. A recent cross-sectional analysis of psychological distress among mothers and expectant women in Saudi Arabia showed significantly high levels of psychological distress, with the educational status of the participant women being inversely proportional to their distress levels [15].…”
Section: Introductionmentioning
confidence: 99%
“…The media play a key role in disseminating accurate information about COVID-19 (23,24). Research has shown that people tend to have a poor awareness of protective measures against certain diseases and this deficiency can have major effects on how well they fare in situations like pandemics.…”
Section: Introductionmentioning
confidence: 99%